Conducting action research for business and management students - Coghlan, David; Shani, Abraham B. (Rami); Lee, Bill; Saunders, M. N. K.; Narayanan, V. K. (Veekay) (London : SAGE Publications Ltd, 2018)
In Conducting Action Research, Coghlan and Shani explain how action research differs from more detached research methods and provides expert guidance on how to engage effectively with it, helping the reader to complete both a successful research project and produce findings that are useful in an organizational context. Ideal for Business and Management students reading for a Master's degree, each book in the series may also serve as reference books for doctoral students and faculty members interested in the method. Part of SAGE's Mastering Business Research Methods, conceived and edited by Bill Lee, Mark N. K. Saunders and Vadake K. Narayanan and designed to support researchers by providing in-depth and practical guidance on using a chosen method of data collection or analysis. Watch the editors introduce the Mastering Business Research Methods series.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Action research; Business -- Research -- Methodology; Management -- Research -- Methodology